Pengaruh Inflasi, Nilai Tukar Rupiah, BI Rate Terhadap Net Asset Value Reksa Dana Saham Syariah - Ainur Rachman; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to examine the influence of inflation, Rupiah exchange rate, and BI rate towards Net Asset Value (NAV) Sharia Equity Fund from January 2011 through December 2014. This research used the quantitative approach method. The analysis techniques used is multiple linear regression and the equation is Y = 12,081-1,755(I)-0,131(RER)-84,492(BI rate).Based on the result of t-test, the rupiah exchange rate has a significant influence by the value -3,017. Inflation and BI rate partially has not significant influence to Net Asset Value (NAV) Sharia Equity Fund with result t -0,144 for Inflation and -1,431 for BI rate. The result of simultaneous test showed that inflation, rupiah exchange rate, and BI rate has significant effect to Net Asset Value (NAV) Sharia Equity Fund with significance value 0,004. Thesuggestions was investment manager is to keep attention to macro economic factors such as inflation, rupiah exchange rate, and BI rate. In order to invest in sharia equity fund can contribute a maximum profit.